Monitoring of vegetable production in greenhouses in the city of Pampas in the province of Tayacaja in the Huancavelica region - Pariona Asto , Ángelo Pedro (2022)
In this paper, the authors designed and implemented a prototype using temperature and humidity sensors to monitor the production of vegetables in greenhouses in the province of Tayacaja. For this, an Arduino board and block programming based on the mBlok software were used. There is a friendly interface for monitoring environmental conditions related to greenhouse temperature and humidity; set between the ranges of (13-17) ° and (60-80)% respectively. In the development of the prototype, it is based on four steps: understanding the problem, plan of activities, execution of activities and test or evaluation of the solution. This work was developed in the Information Management course with students of the II cycle of the industrial engineering career.